Study of Ionospheric TEC from GPS observations and comparisons with IRI and SPIM model predictions in the low latitude anomaly Indian subcontinental region - Panda, S. K.; Gedam, S. S.; Rajaram, G. (My University, 2015)
The present study investigates variation of the ionospheric total electron content (TEC) in the low latitude Indian sub-continental region from the GPS observations and its comparison with the global ionosphere maps (GIMs), standard international reference ionosphere (IRI 2012), and the standard plasmasphere–ionosphere model (SPIM) for the period from November 2011 to October 2012 that corresponds to the progressive phase towards the midst of the solar cycle-24. Observations during quiet period show diurnal maximum of TEC occurring around 14:00–16:00 IST, with relatively broader and longer duration of local maximum at Bangalore and behave reversely towards Delhi. The secondary maximum of TEC was markedly noticeable at Bangalore during the months of March and September, and only in the month of September at Hyderabad and Mumbai. However, the relatively higher TEC during December month than the June is ascribed to the winter anomaly which is more prevalent during the high solar activity periods. The prevailing instability in latitudes of anomaly crest during January 2012 is possibly due to the seasonal variation of lunar tidal effects, modulating the EEJ strength at the equator. The studies covered the period of a strong geomagnetic storm during 6–11 March 2012 (SYM-H: −149 nT) which resulted in positive deviation of GPS-TEC at Bangalore (↑ 20%), Hyderabad (↑ 22%), and Lucknow (↑ 94%) compared to the mean quiet days level. The relatively large deviation of TEC at Lucknow could be attributed to the poleward shifting of the anomaly crest, manifested by enhanced fountain effect at the equator. Studies confirm excellent agreement (80–85%) of GPS-TEC with IGS-GIM at Bangalore and Hyderabad with the exception of the night-time hours (Deviations >50%). However relatively larger deviation of GPS-TEC from GIM-TEC at Delhi could be due to the unavailability of IGS stations in the proximity of the position. Predictions of the SPIM model (extension of IRI up to GPS altitude) exhibit much higher deviation from the in situ GPS observations as well as GIM and IRI outputs during quiet periods. Correspondingly, either of the models (IRI and SPIM) did not respond well to the arrival of the sudden storm commencements (SSCs) during the storm period (6–11 March 2012). When SPIM is used instead of IRI, the overestimation from GPS-TECs are further exaggerated by 13–18% (December solstice), 27–37% (March equinox), 15–31% (June solstice), and 20–32% (September equinox) during peak hours of the period. We attribute the relatively more deviation of the SPIM than the IRI model possibly due to its plasmaspheric extension to the IRI model by adding the Russian SMI model of high latitude characteristics. Hence, we emphasize the further improvement in the model with due consideration of the driving forces at play in the region, for reliable predictions of the low latitude ionosphere.
Keywords: Ionosphere; Total electron content; GPS; TEC; EIA region; IRI; SPIM